The Corruption Formula: Possibilities of Corruption in Government Service Delivery in Liberia - P. Nyeleker, Kerkulah; Dian Fridayani, Helen; Chiang, Li-Chun (Policy & Governance Review, 2025)
Corruption in government services has become a relevant topic of study. This study examines the possibility of corruption in Liberian government services. Previous analyses are still limited to identifying the specific possibilities driving corruption in government services in developing countries. This study uses a qualitative method with a case study approach guided by the Corruption Formula theory across three indicators: monopoly of power (M), discretion by officials (D), and lack of accountability (A), expressed as C=M+D-A. PPrimary data were collected through in-depth interviews with key informants. Secondary data were collected from documentation, journals, newspapers, etc., and analyzed using NVIVO 12 Plus software. The findings revealed the following: (1) service providers have a high monopoly over services, as they often use their dominant positions for personal gain; (2) there is a lot of discretion by officials, giving them the freedom to manipulate systems and engage in illicit activities without clear oversight; and (3) there is limited accountability to hold individuals and institutions answerable for their actions, as officials constantly engage in wrongdoings without facing legal consequences. This study closes the gap in understanding corruption in government services with evidence from Liberia, emphasizing the need for policymakers to enhance the integrity of public services.